Alterações ambientais independentes da resposta: um estudo sobre desamparo aprendido, comportamento supersticioso e o papel do relato verbal - Magalhães, Karine Amaral (2006)
This study attempted to produce learned helplessness with humans subjects exposed to controllable and to incontrollable events. Two experiments were carried out. Experiment 1 investigated the effects of a procedure similar to one used by Hatfield & Job (1998) on the production of learned helplessness. In this procedure, differently from the most common used on the distribution of the aversive stimuli for the yoked group, the order of the stimuli (strident sounds) presentation was randomized with the intent of preventing concentration of stimuli with a certain characteristic (short duration) at some specific moments of training. Experiment 2 tried to investigate the effects of requesting verbal reports about the working contingencies during some trials of the training on learned helplessness. Experiment 1 had 28 participants, distributed into 3 groups: Contingent (9 participants), Yoked (9 participants), and Control (10 participants). During training, pressing F1 3 times eliminated the sound for the Contingent group; during test, pressing 3 times one of the 3 rectangles (the one on the left) presented on a computer keyboard eliminated the sound. For the Yoked group, during training none of the available responses could eliminate the sound, and during test pressing 3 times the left rectangle could eliminate the sound. Control group was submitted only to test and the response that eliminated the sound was the same as for the other groups during test. In Experiment 1, during training, sounds were presented 40 times for each participant and during test another 40 times. Experiment 2 had 20 participants distributed into two groups: Contingent Verbal Report (10 participants) and Yoked Verbal Report (10 participants). The procedure for these two groups was the same as for Contingent and Yoked groups in Experiment 1, except that for 8 trials during training participants were asked to give verbal reports describing the working contingencies. Results of Experiment 1 show that the procedure used with the Yoked group of changing the order of sounds duration prevented concentration of short duration sounds in the final trials of training and also prevented superstitious behavior. In relation to learned helplessness, although more participants in Yoked group than in Contingent and Control groups learned the requested response to eliminate the sound, learned helplessness in its sharpest mode (not learning) was observed in one participant performance, and in its moderate mode (learning difficulty) was observed in two participant performance. Notwithstanding, the Yoked group did not statistically differ from Contingent and Control groups. Experiment 2 replicated results of Experiment 1 in relation to Yoked Verbal Report group s procedure. In relation to learned helplessness, again results resemble Experiment 1 s in that although more participants in the Yoked Verbal Report group than in Contingent Verbal Report group learned the required response, learned helplessness was observed in two participants in its most sharpened mode, and in other two participants performance in its moderate mode. For both Yoked groups in total, seven participants presented learned helplessness in some way, and for 12 participants (63% of total number of participants exposed to uncontrollable aversive stimulus) no prejudice of learning was observed. Therefore, none of the two experiments produced learned helplessness with humans and statistical analysis confirm this result. In relation to verbal reports, 60% of the participants in each group reported the planned contingency at some moment. For four out of five participants in the Yoked Verbal Report group that described the planned contingency, that is, uncontrollability, learned helplessness was in some mode observed